Bilobalide Induces Apoptosis in 3T3-L1 Mature Adipocytes through ROS-Mediated Mitochondria Pathway - Su Bu; Anran Xiong; Zhiying Yang; Faycal Aissa-Brahim; Ying Chen; Yichun Zhang; Xunyong Zhou; Fuliang Cao (Molecules, 2023)
Bilobalide exhibits numerous beneficial bioactivities, including neuroprotective, anti-inflammatory, and antioxidant activity. Our previous study demonstrated that bilobalide inhibits adipogenesis and promotes lipolysis. The dose-dependent cytotoxicity was found to be specific to the mature adipocytes only, indicating the potential for regulating apoptosis in them. Herein, we aimed to investigate the apoptotic effects of bilobalide on 3T3-L1 mature adipocytes and elucidate the underlying mechanisms thereof. Flow cytometry analysis (FACS) revealed the pro-apoptotic effects of bilobalide on these cells. Bilobalide induced early apoptosis by reducing the mitochondrial membrane potential (MMP). DNA fragmentation was confirmed using TUNEL staining. Additionally, bilobalide increased the intracellular reactive oxygen species (ROS) levels and activities of Caspases 3/9. Pre-treatment with NAC (an ROS scavenger) confirmed the role of ROS in inducing apoptosis. Moreover, bilobalide up- and down-regulated the expression of Bax and Bcl-2, respectively, at the mRNA and protein expression levels; upregulated the Bax/Bcl-2 ratio; triggered the release of cytochrome c from the mitochondria; and increased the protein expression of cleaved Caspase 3, cleaved Caspase 9, and PARP cleavage. These results support the conclusion that bilobalide induces apoptosis in mature 3T3-L1 adipocytes through the ROS-mediated mitochondrial pathway, and offers potential novel treatment for obesity.